2023
DOI: 10.1002/adem.202300037
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Straw Aerogel Thermal Insulation Materials

Abstract: Biogenic wheat straw is a carbon‐storing building insulation material. However, the enzymatic hydrolysis ratio of its cellulose is relatively low due to the presence of hemicellulose and lignin hindering its thermal insulation performance. Herein, aerogel and straw composites are reported with thermal conductivity of 35 mW m−1 K−1, while high‐cellulose fiber conversion in straw is obtained using a hybrid mechanical and chemical process. Furthermore, it is shown that the in situ cellulose‐reinforced silica aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…(c) Plots of thermal conductivity versus density of the APD-COSC aerogels. (d) Comparison plots of thermal conductivity and density for APD-COSC aerogels and other aerogels recently reported. (e) Comparison plots of BET-specific surface area and mesopore volume for the APD–COSC aerogels and other aerogels recently reported. (f–i) SEM images showing the cross-sectional morphology of APD-COSC 25/75, APD-COSC 10/90, APD-COSC 05/95, and APD-COSC 0/100. Upper right images showing the corresponding water contact angle at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…(c) Plots of thermal conductivity versus density of the APD-COSC aerogels. (d) Comparison plots of thermal conductivity and density for APD-COSC aerogels and other aerogels recently reported. (e) Comparison plots of BET-specific surface area and mesopore volume for the APD–COSC aerogels and other aerogels recently reported. (f–i) SEM images showing the cross-sectional morphology of APD-COSC 25/75, APD-COSC 10/90, APD-COSC 05/95, and APD-COSC 0/100. Upper right images showing the corresponding water contact angle at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In this context, wheat straw's cellulose network plays a pivotal role in enhancing the mechanical strength and durability of aerogel/cellulose composites, while the aerogel itself serves as the primary agent in lowering the thermal conductivity of these innovative materials. 7,8 This synergy between wheat straw and aerogel opens up new avenues for the development of thermal insulation materials that are not only eco-friendly but also highly efficient in reducing heat transfer. As we continue to seek sustainable solutions to combat climate change and promote environmental responsibility, the utilization of wheat straw in conjunction with advanced materials like aerogel represents a compelling step forward in addressing the multifaceted challenges of our times.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wheat straw, a readily available agricultural waste product, has recently gained substantial recognition for its potential to mitigate carbon emissions within the construction industry. This versatile crop residue, remaining in abundance after the wheat harvest, emerges as a sustainable and environmentally friendly resource for the sequestration of carbon dioxide, a prominent contributor to the ongoing challenge of climate change. Furthermore, the incorporation of agricultural wheat straw into aerogel materials has shown significant promise. , In this context, wheat straw’s cellulose network plays a pivotal role in enhancing the mechanical strength and durability of aerogel/cellulose composites, while the aerogel itself serves as the primary agent in lowering the thermal conductivity of these innovative materials. , This synergy between wheat straw and aerogel opens up new avenues for the development of thermal insulation materials that are not only eco-friendly but also highly efficient in reducing heat transfer. As we continue to seek sustainable solutions to combat climate change and promote environmental responsibility, the utilization of wheat straw in conjunction with advanced materials like aerogel represents a compelling step forward in addressing the multifaceted challenges of our times.…”
Section: Introductionmentioning
confidence: 99%
“…Alaa Rashad M [16] found that gel insulation materials with low thermal conductivity and good compressive strength could be prepared by combining fly ash, metakaolin, hydrated lime and gypsum with a small amount of silica fume and graphite. Jadhav P S [17] found that adding 50% aerogel to biomass wheat straw can effectively reduce the thermal conductivity of the composite material and improve its thermal insulation and mechanical properties. An L. [18] found that the use of aerogel and ceramics to prepare ceramic nanocomposites has good high temperature resistance, and the thermal conductivity is only 0.024 W/(m•K).…”
Section: Introductionmentioning
confidence: 99%